2003
DOI: 10.1016/s0006-3495(03)74752-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Type I Collagen Surface Density on Fibroblast Spreading, Motility, and Contractility

Abstract: We examine the relationships of three variables (projected area, migration speed, and traction force) at various type I collagen surface densities in a population of fibroblasts. We observe that cell area is initially an increasing function of ligand density, but that above a certain transition level, increases in surface collagen cause cell area to decline. The threshold collagen density that separates these two qualitatively different regimes, approximately 160 molecules/ microm(2), is approximately equal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
166
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(192 citation statements)
references
References 35 publications
(40 reference statements)
18
166
2
1
Order By: Relevance
“…In particular, it can be reproduced in vitro by adding saturating amounts of matrix components, that extinguish substrate inhomogeneities. At this regard, experimental evidence have demonstrated that, consistently with our results, cells cultured in matrices with high collagen densities show a dramatic downregulation of their migratory capacity, driven by the fact that their integrin receptors are completely engaged without maximal cell spreading and movement [20,22]. An analogous behavior is seen by varying the cell proteolytic activity, measured by the parameter χ p , see Fig.…”
Section: Resultssupporting
confidence: 89%
“…In particular, it can be reproduced in vitro by adding saturating amounts of matrix components, that extinguish substrate inhomogeneities. At this regard, experimental evidence have demonstrated that, consistently with our results, cells cultured in matrices with high collagen densities show a dramatic downregulation of their migratory capacity, driven by the fact that their integrin receptors are completely engaged without maximal cell spreading and movement [20,22]. An analogous behavior is seen by varying the cell proteolytic activity, measured by the parameter χ p , see Fig.…”
Section: Resultssupporting
confidence: 89%
“…Recently it has been demonstrated in the literature that these effects can be expressed in the cell at the level of genomic regulation, thus contributing to very fundamental changes in cellular physiology, ultimately resulting in unknown adjustments to cellular proliferation, motility and, in some cases, phenotype [17][18][19][20][21][22][23]. In this work we have demonstrated that measurements of cellular proliferation and viability on coated spectroscopic substrates can be correlated with spectral changes induced by adjustments to cell physiology when cultured on the different coatings.…”
Section: Resultsmentioning
confidence: 67%
“…Noninvasive spectroscopic measurements of cellular function in in-vitro cultured cell lines require substrates such as quartz, ZnSe and MirrIR (Ag/SnO 2 coated glass for FTIRM from Kevley Technologies) etc. It has been demonstrated that surfaces and scaffolds for cell culture can induce changes in cellular adhesion and motility [17,18], in their proliferation and differentiation [16,19], and in gene expression [20], ultimately influencing the fate of the cell [21]. Much of the interaction of adherent cells with their culture substrates is dependent on the surface chemistry [18,22] and surface energy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cell migratory ability can be also determined by the absolute concentrations of ECM components: this mechanism is called haptokinesis. At this regard, several experimental studies show that cell speed, spreading, and membrane activity is maximal at intermediate levels of ECM densities, both on 2D substrates [14,19] and in 3D matrices [73]. Also the local rigidity of the matrix plays a fundamental role in determining the efficiency and the direction of cell crawling, e.g.…”
Section: Discussionmentioning
confidence: 99%